Miejsce ludzi starszych w procesie wychowania młodzieży według Jana Chryzostoma - Kołosowski, Tadeusz (Vox Patrum, 2009)
From the analysis of chosen writings of St. John Chrysostom results that the Author as pastor and the moralist observes critically the attitude of many representatives of the older generation. At these people the external grey hair is not matched by the internal grey, this means the ripe old age and the increasing vital experience develops at them the power of the faith and beautiful and worthy Christian manner of life. Such people in vain await esteem from the younger generation. Older people can gain esteem at young people, if live in the manner morally beautiful. Then they can transfer the young people their own experience and be for them the good example.